2021
DOI: 10.1021/acs.jpclett.1c02273
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Based Feature Makes Machine Learning Cognizing Crystal Properties Simple

Abstract: Machine learning (ML) accelerates the rational design and discovery of materials, where the feature plays a critical role in the ML model training. We propose a low-cost electron probability waves (EPW) descriptor based on electronic structures, which is extracted from highsymmetry points in the Brillouin zone. In the task of distinguishing ferromagnetic or antiferromagnetic material, it achieves an accuracy (ACC) at 0.92 and an area under the receiver operating characteristic curve (AUC) at 0.83 by 10-fold cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…26 In contrast to traditional methods, ML does not rely on the development of any prior physical knowledge (e.g., Debye temperature or phonon dynamics properties) 27 but utilizes data to explore the physical rules, showing outstanding performances in scientic research and industrial design. [28][29][30][31][32][33][34][35][36][37][38] Stanev et al reported ML models to explore the rule of the superconducting transition temperature. 39 Xie et al applied the sure independence screening and sparsifying operator (SISSO) approach to search for mathematical formulas related to superconductivity with smaller errors.…”
Section: Introductionmentioning
confidence: 99%
“…26 In contrast to traditional methods, ML does not rely on the development of any prior physical knowledge (e.g., Debye temperature or phonon dynamics properties) 27 but utilizes data to explore the physical rules, showing outstanding performances in scientic research and industrial design. [28][29][30][31][32][33][34][35][36][37][38] Stanev et al reported ML models to explore the rule of the superconducting transition temperature. 39 Xie et al applied the sure independence screening and sparsifying operator (SISSO) approach to search for mathematical formulas related to superconductivity with smaller errors.…”
Section: Introductionmentioning
confidence: 99%